Performance analysis of selection combining for amplify-and-forward cooperative diversity networks over weibull fading channels - Yuejun Lei; Weijun Cheng; Zhimin Zeng (2009 IEEE International Conference on Communication Technology and Applications, 2009)
In this paper, we investigate cooperative diversity using amplify-and-forward (AF) relaying over independent and identically distributed (i.i.d.) Weibull fading channels with selection combining (SC) and derive a approximate closed form expression for the probability density function (PDF) of the signal-to-noise ratio (SNR) for the Weibull fading distribution, Then closed form expression for the average symbol error probability (ASEP), the outage probability, the average channel capacity and the moment of average SNR are obtained. Computer simulations are also performed to verify the analytical results.